MANUAL OF SHORT-TERM SEA ICE FORECASTING - Wittmann, Walter I.; MacDowell, Gordon P. (1964)
The intent of this manual is to describe in as great detail as possible the procedures and techniques hitherto developed in provision of short- term ice forecasts. The procedures are formulated for application; all ice features to be predicted are correlated with known or readily predictable environmental variables.